Investment : Specific Technology Shocks and International Business Cycles; An Empirical Assessment. (IMF Working Papers; Working Paper, 2010)
In this paper, we first introduce investment-specific technology (IST) shocks to an otherwise standard international real business cycle model and show that a thoughtful calibration of them along the lines of Raffo (2009) successfully addresses the "quantity", "international comovement", "Backus-Smith", and "price" puzzles. Second, we use OECD data for the relative price of investment to build and estimate these IST processes across the U.S and a "rest of the world" aggregate, showing that they are cointegrated and well represented by a vector error correction model (VECM). Finally, we demonstrate that when we fit such estimated IST processes in the model instead of the calibrated ones, the shocks are actually not as powerful to explain any of the four montioned puzzles.